An evaluation of career guidance programs given to high school pupils in Harare Urban - Munongwa, Frank M. (Midlands State University, 2017)
The foundations of career management skills should be laid at an early age and as students move from primary to high or secondary schools, there should be a general idea of what they want to do and should be further equipped in high schools with the relevant self management skills such as, problem solving, career planning, decision making, time management, learning and information management, in preparation for their future careers. Of concern also to note is that within general education pathways, substantial career guidance and counseling time is spent preparing students to choose and compete for tertiary education places. This may result in those not intending to enter tertiary education receiving little or no help.